Pengaruh Debt To Equity Ratio (DER) dan Debt To Asset Ratio (DAR) Terhadap Kinerja Perusahaan Manufaktur Subsektor Makanan Dan Minuman Di Bursa Efek Indonesia Tahun 2014-2020 - Wiranawata, Hilmi (MAMEN: Jurnal Manajemen, 2022)
This study discusses the effect of debt to equity ratio (DER) and debt to asset ratio (DAR) on the performance of manufacturing companies in the food and beverage subsector (IDX). The number of samples in this study was 9 companies for the period 2014-2020 using the purposive sampling method. The analytical method used is panel data regression. From the analysis results, the regression equation shows Y = 0.981005+ 17.17332 (X1) – 9.277439 (X2). The results show that partially for the Debt to Equity Ratio (X1) variable at tcount > ttable or 2.993297 > 2,00098, it means Debt to Equity Ratio has a significant positive effect on Return On Equity. The Debt To Asset Ratio (X2) variable obtained a value of tcount < ttable or -0.497922 < 2,00098, meaning that the Debt To Asset Ratio has no significant effect on Return On Equity. Based on the F test, the value of Fcount > Ftable or 6, 913 > 3.15 means that DER and DAR simultaneously have a significant effect on ROE. The value of the coefficient of determination R Square (R2) of 0.187281 indicates that 18% of the contribution of ROE from the DER and DAR structures while the remaining 82% is influenced by other variables not included in the regression model in this study.